Mediation of Extracellular Polymeric Substances in Microbial Reduction of Hematite by Shewanella oneidensis MR-1 - Gao, Lei; Lu, Xiancai; Liu, Huan; Li, Juan; Li, Weijie; Song, Rongbin; Wang, Ruiyong; Zhang, Dongmei; Zhu, Junjie (Frontiers in Microbiology, 2019)
Extracellular electron transfer (EET) plays a fundamental role in microbial reduction/oxidation of minerals. Extracellular polymeric substances (EPS) surrounding the cells constitute a matrix that separates the cell’s outer membrane from insoluble minerals. The present study investigated the effect of EPS on EET processes during microbial reduction of hematite by the iron-reducing strain Shewanella oneidensis MR-1 (MR-1). Electrochemical characterization techniques were employed to determine the influence of EPS components on the redox ability of MR-1. Cells removed EPS exhibited approximately 30% higher hematite reduction than regular MR-1 cells, and produced a current density of 56 μA cm-2, corresponding to 3–4 fold that of regular MR-1. The superior EET of EPS-deprived cells could be attributed to direct contact between outer membrane proteins and hematite surface, as indicated by more redox peaks being detected by cyclic voltammetry and differential pulse voltammetry. The significantly reduced current density of MR-1 cells treated with proteinase K and deoxyribonuclease suggests that the electron transfer capacity across the EPS layer depends mainly on the spatial distribution of specific proteins and electron shuttles. But exopolysaccharides in EPS tend to inhibit electron transfer although they favor the attachment of cells onto solid surface. Consistently, the charge transfer resistance of cells lacking EPS was only 116.3 Ω, or 44 times lower than that of regular cells (5,139.1 Ω). These findings point to a negative influence of EPS on EET processes for microbial reduction/oxidation of minerals.